Proceedings 16th International Parallel and Distributed Processing Symposium 2002
DOI: 10.1109/ipdps.2002.1016488
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the NAS benchmark MG in SAC

Abstract: SAC is a purely functional array processing language designed with numerical applications in mind. It supports generic, high-level program specifications in the style of APL. However, rather than providing a fixed set of builtin array operations, SAC provides means to specify such operations in the language itself in a way that still allows their application to arrays of any dimension and size. This paper illustrates the specificational benefits of this approach by means of a high-level SAC implementation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Several case studies have shown that simple recompilation of SaC code yields speedups that are competitive with manually parallelized imperative programs. High sequential performance allows implicitly parallelized SaC code to substantially outperform even hand-optimized sequential imperative programs Grelck, 2002;Grelck & Scholz, 2003b;Grelck & Scholz, 2003a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several case studies have shown that simple recompilation of SaC code yields speedups that are competitive with manually parallelized imperative programs. High sequential performance allows implicitly parallelized SaC code to substantially outperform even hand-optimized sequential imperative programs Grelck, 2002;Grelck & Scholz, 2003b;Grelck & Scholz, 2003a).…”
Section: Resultsmentioning
confidence: 99%
“…In order to quantify the impact of individual design decisions on the parallel performance of compiled SaC code we restrict ourselves to a set of representative micro benchmarks. Readers looking for more general case studies on programming methodology and runtime performance in comparison with other programming environments are referred elsewhere Grelck, 2002;Grelck & Scholz, 2003b;Grelck & Scholz, 2003a). Experiments have been made on three different machine architectures: a 4-processor SUN E650, a 12processor SUN E4000, and a 72-processor SUN E15k.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Where this separation does not prevail, for example in high‐performance computing, often applications internally apply the same functions to arguments of different shape in a way that is difficult to deduce statically even if the initial shapes are indeed known. Examples here are the NAS benchmarks MG and FT .…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…For certain applications, predominantly numerical applications on large homogeneous data structures, these languages can deliver parallel performance competitive if not superior to that of hand-coded Fortran programs [2,4,7,9]. The beauty of this approach is that it is completely implicit and thus avoids all the usual pitfalls of concurrent programming such as deadlocks or race conditions.…”
Section: Introductionmentioning
confidence: 99%